Developing Science Learning Media: Hainthec Quartet Cards(Harmony in the Ecosystem) - Nia, Feriyani Rahman; Khotimah, Khusnul; Hidayat , Taufik (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
In the science learning of harmony in ecosystem material, students still have difficulty in understanding the abstract concepts in the harmony in ecosystem material. The purpose of this study is to determine the development process, media feasibility and student responses. The research method used is the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The results of the feasibility test of this study by three media experts obtained an average percentage of 89.16% with a very feasible category. The results of the feasibility test by three material experts obtained an average percentage of 93.33% with a very feasible category. The results of the feasibility test by three language experts obtained an average percentage of 90.22% with a very feasible category. The results of the small group student response questionnaire obtained an average percentage of 90.48% with a very feasible category, the results of the large group student response questionnaire obtained an average percentage of 87.74% with a very feasible category and the results of the teacher response questionnaire obtained an average percentage of 92% with a very feasible category, so that the Hainthec quartet card learning media can be used as a learning medium. The conclusion of this study is that the Hainthec quartet card learning media produced received a response that was Very Suitable for use in learning. This is based on assessments by media experts, material experts and language experts as well as responses from small group trial students, large group trial students and teachers. The suggestions of this study are: 1) In the development of the Hainthec quartet card learning media, the media is still made using the usual (free) Canva application. 2) It is necessary to pay attention to suggestions and input from experts. 3) Pay more attention to the material contained in the learning media to minimize errors.